THE INFLUENCE OF ORGANIZATIONAL CLIMATE AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Dijah Julindrastuti; Iman Karyadi (SEAN Institute, 2023)
This research is motivated by the desire and hope of the organization to be able to develop and be able to achieve the expected goals, where one of the factors comes from the organization's employees. Organizational climate and job satisfaction can influence an employee's performance. Based on this description, this research was conducted to determine the influence organizational climate and job satisfaction on employee performance. This research is quantitative research with a causal comparative nature using survey methods. The population in this study were non-educational employees at Wijaya Kusuma University, Surabaya, with a population of 75 non-educational employees and a sample of 50 employees. Sampling used purposive sampling technique. The research data collection technique was carried out through questionnaires. Data analysis techniques include validity and reliability tests, descriptive data analysis, Multiple Regression Analysis. The results of this research are 1) Organizational climate has a positive and significant effect on employee performance 2) Job satisfaction has a positive and significant effect on employee performance